1987
DOI: 10.3181/00379727-186-3-rc1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Tumor Cell Induced Platelet Aggregation by Antibodies to Platelet Glycoproteins lb and llb/llla

Abstract: Tumor cell induced platelet aggregation was shown to be inhibited in a dose dependent manner by preincubation of human platelets with antibodies to platelet glycoprtein Ib and the Ilb/llla complex. Combination of antibody to Ib and antibody to the Ilb/llla complex at concentrations which produced half maximal inhibition of platelet aggregation alone caused complete inhibition of tumor cell induced platelet aggregation. Antibodies to platelet glycoproteins Ib and the Ilblll la complex also inhibited platelet sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 5 publications
(8 reference statements)
0
32
0
Order By: Relevance
“…68 Due to its specific expression in MKs and platelets, GPIba could become an attractive target for the development of new skeletal metastasis therapies. However, controversies have been raised in the past for the role of GPIba in tumor cell-induced platelet aggregation, with some reports showing its positive contribution, 69 whereas others described no impact of blocking GPIba antibodies. 70 Also, in an experimental metastasis model using B16F10 melanoma cells, mice lacking GPIba developed a lower number of lung metastases than WT mice, 71 whereas functional inhibition of GPIba using monoclonal antibodies in vivo led to a strong increase in pulmonary metastasis.…”
Section: Platelets Megakaryocytes and Metastasis 27mentioning
confidence: 99%
“…68 Due to its specific expression in MKs and platelets, GPIba could become an attractive target for the development of new skeletal metastasis therapies. However, controversies have been raised in the past for the role of GPIba in tumor cell-induced platelet aggregation, with some reports showing its positive contribution, 69 whereas others described no impact of blocking GPIba antibodies. 70 Also, in an experimental metastasis model using B16F10 melanoma cells, mice lacking GPIba developed a lower number of lung metastases than WT mice, 71 whereas functional inhibition of GPIba using monoclonal antibodies in vivo led to a strong increase in pulmonary metastasis.…”
Section: Platelets Megakaryocytes and Metastasis 27mentioning
confidence: 99%
“…Similarly, Kitagawa et al [132] demonstrated that the etlIb[33 complex on the platelet surface was involved in both thrombin-dependent and independent platelet aggregations induced by tumor cells. The Gplb may also be important since antibodies to this glycoprotein were shown to inhibit TCIPA [130,132], although different observations were made by Karpatkin et al [133].…”
Section: Formation Of Irreversible Tumor Cell-platelet Aggregatesmentioning
confidence: 99%
“…The potential role of aIIb[33 in TCIPA came to light when Grossi et al [130] and Bastida et al [131] first independently demonstrated that treatment of platelets with antibodies to platelet Gplb or alIb[33 inhibited TCI-PA, suggesting that the platelet ~tlIb[33 integrin receptor is required for TCIPA. These results were subsequently confirmed by others [132,133].…”
Section: Formation Of Irreversible Tumor Cell-platelet Aggregatesmentioning
confidence: 99%
“…Whereas some groups have not perceived diminished interactions on blockade of GPIb␣, 12 early experiments performed by other groups do suggest a role of GPIb␣ in at least some phases of TCIPA. 37,38 Similarly controversial results have been obtained when GPIb␣ functions in experimental metastasis were studied in vivo. Whereas reduced experimental pulmonary metastasis was observed in mice lacking GPIb␣, 39 functional inhibition of GPIb␣ by monovalent, monoclonal antibodies led to a strong increase in pulmonary melanoma metastasis in vivo 16 (Figure 2).…”
mentioning
confidence: 99%
“…53,54 Of all platelet receptors mentioned in this review, GPIIb/IIIa probably has the longest career as a metastasis-related molecule. As early as 1987, the role of GPIIb/IIIa in TCIPA was established, 37,38 and a year later the importance of this integrin for tumor cell-platelet interactions was shown for several different tumor cell lines, among them 2 colon cancer cell lines as well as B16 melanoma cells (Figure 2) and T241 Lewis bladder cells. 12 In the same publication, the in vivo importance of platelet GPIIb/IIIa in models of pulmonary metastasis was unveiled by blockade of GPIIb/IIIa before tumor cell injection with the monoclonal antibody 10E5.…”
mentioning
confidence: 99%